Optimal Temporal Risk Assessment - Balcı, Fuat; Freestone, David; Simen, Patrick; deSouza, Laura; Cohen, Jonathan D.; Holmes, Philip (Frontiers in Integrative Neuroscience, 2011)
Time is an essential feature of most decisions. Keeping track of time is adaptive because the reward earned from decisions frequently depends on the temporal statistics of the environment. Accordingly, evolution appears to have favored a mechanism that predicts intervals in the seconds-to-minutes range with high accuracy on average, but significant variability from trial to trial. Importantly, the subjective sense of time that results is sufficiently imprecise that maximizing rewards can require substantial behavioral adjustments in response to this temporal uncertainty. Reward-maximization in many daily decisions therefore requires optimal temporal risk assessment. Using tasks that entail different decisions and that impose different time constraints on the reward function, we examine temporal risk assessment ability in terms of the degree to which it approaches optimality. We review recent literature and present human and rodent data that strongly support the hypothesis that these animals take normative account of their endogenous timing uncertainty. By incorporating the psychophysics of interval timing into the study of reward maximization, our approach bridges empirical and theoretical gaps between the interval timing and decision making literatures.